2019
DOI: 10.1039/c8tb02967a
|View full text |Cite
|
Sign up to set email alerts
|

Injectable amine functionalized graphene and chondroitin sulfate hydrogel with potential for cartilage regeneration

Abstract: Chemically functionalized graphene covalently reactsin situwith chondroitin sulfate to form an enhanced, injectable hydrogel for potential cartilage therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…As the main component of our hydrogel, CS is capable of promoting cartilage regeneration. [18] Indeed, we found that the precursor solution exhibited the desirable syringeability owing to its low viscosity,w hich enabled the close filling of irregular defects.M oreover,c ascade enzyme complex polymerization endowed the hydrogel with ah igh mechanical strength, thereby rendering it suitable for use as af iller in cartilage repair. Considering the biosafety and mechanical properties of the hydrogel, 8wt% Acryloylated-CS and 3wt% DMAA were selected for further measurements.T he successful gelation of the CS-DMAA hydrogel was also observed in 100 %D ulbeccosM odified Eagle Medium and 20 %( v/v) mouse blood, where the hydrogel formed within 2min in the blood sample.…”
Section: Du ¼mentioning
confidence: 92%
“…As the main component of our hydrogel, CS is capable of promoting cartilage regeneration. [18] Indeed, we found that the precursor solution exhibited the desirable syringeability owing to its low viscosity,w hich enabled the close filling of irregular defects.M oreover,c ascade enzyme complex polymerization endowed the hydrogel with ah igh mechanical strength, thereby rendering it suitable for use as af iller in cartilage repair. Considering the biosafety and mechanical properties of the hydrogel, 8wt% Acryloylated-CS and 3wt% DMAA were selected for further measurements.T he successful gelation of the CS-DMAA hydrogel was also observed in 100 %D ulbeccosM odified Eagle Medium and 20 %( v/v) mouse blood, where the hydrogel formed within 2min in the blood sample.…”
Section: Du ¼mentioning
confidence: 92%
“…[ 136 ] In fact, GO can be added to various biomaterials such as silk fibroin hydrogel, chondroitin sulfate hydrogel, composite hydrogel of calcium alginate/PAM, and polycaprolactone scaffolds to improve mechanical behaviors and mimic natural cartilage. [ 137–140 ] Hybrid scaffold methacrylated chondroitin sulfate (CSMA)/poly(ethylene glycol) methyl ether‐ε‐caprolactone‐acryloyl chloride (PECA)/GO developed by Liao et al. [ 141 ] possessed good viscoelasticity, conductivity, as well as cartilage cell adhesion and proliferation in vitro and achieved the best reparative effect in an animal study to repair full‐thickness cartilage defect.…”
Section: Cartilage Repairmentioning
confidence: 99%
“…This approach was demonstrated for hydrogels based on GO and either collagen [ 111 ] or poly-D,L-lactic acid/polyethylene glycol [ 112 ], designed to repair the cartilage. Chondroitin sulfate in another biomolecule of interest to promote regeneration of this tissue, and to this end it was crosslinked with a chemically modified GO, to yield a hydrogel that effectively stimulated the deposition of a collagen matrix from mesenchymal stem cells [ 113 ]. Hydroxyapatite is another useful component of natural origin to yield biomaterials to repair the cartilage, as shown for a hydrogel with GO and polyvinyl alcohol that was 3D printed and displayed excellent biomechanical and bio-friction properties [ 114 ].…”
Section: Recent Advancements On Hydrogels With Carbon Nanomaterials For Medicinementioning
confidence: 99%